Effects of edge-stiffened web openings on the behaviour of cold-formed steel channel sections under compression. (November 2019) - Chen, Boshan; Roy, Krishanu; Uzzaman, Asraf; Raftery, Gary M.; Nash, David; Clifton, G. Charles; Pouladi, Pouya; Lim, James B.P.
Abstract: The use of cold-formed steel (CFS) channel sections are becoming popular as the load-carrying members in building structures, and such channel sections often include web openings for the ease of installation of services. Traditional web openings are normally punched, and are unstiffened which can restrict the size and spacing of web openings. Recently, a new generation of CFS channel sections with edge-stiffened web openings has been developed, and is widely used in New Zealand. However, no experimental investigation has been reported in the literature for such channel sections under compression. In this paper, a total of 75 results comprising 26 axial compression tests and 49 finite element analysis results are reported on the compression resistance of CFS channel sections with both edge-stiffened and unstiffened web openings. For comparison, channel sections without web openings were also tested. For all specimens, initial imperfections were measured using a laser scanner. A nonlinear elasto-plastic finite element model was also developed, and the results showed good agreement with the test results. A parametric study was conducted using the validated finite element model to investigate the effect of opening spacing and column length on compression resistance of channel sections. It is shown that for the case of a channel section having seven edge-stiffened web openings, the compression resistance increased by as much as 22%, compared to a plain channel section. For comparison, the same section having unstiffened web openings had a 20% reduction in compression resistance, compared to a plain channel section. Highlights: A new generation of cold formed steel sections with edge stiffened holes is examined. Results from an experimental regime and elasto-plastic finite element are reported. Local and overall imperfections are considered in FE models. Edge stiffened hole-sections can outperform plain sections in terms of axial strength. A parametric study demonstrating the effect of opening spacing and column length was conducted.